Latest news concerning the Armenian and Syrian sufferers, May 24, 1916 (American Committee for Armenian and Syrian Relief, 1916)
I. Winter in the Russian Caucacus -- II. The return to Van. -- III. Hardships of the Syrians in Persia. -- IV. Missing Nestorian group reported massacred -- V. Relief work in the Turkish empire (1. Extent of the catastrophe; 2. Needs of the survivors; 3. Way for Relief now open) -- VI. Financial statement.